Correlations between the phenolic and fibre composition of mushrooms and the glycaemic and textural characteristics of mushroom enriched extruded products. (January 2020) - Lu, Xikun; Brennan, Margaret A.; Narciso, Joan; Guan, Wenqiang; Zhang, Jie; Yuan, Li; Serventi, Luca; Brennan, Charles S.
Abstract: In this study, semolina extruded snack products were supplemented with white button mushroom (Agaricus bisporus), shiitake (Lentinula edodes) and porcini mushrooms (Boletus edulis). The functional properties of the products were analysed, including the nutritional profile, starch characteristics (content, gelatinisation and digestibility) and antioxidant activities (total phenolic content, DPPH and ORAC), colour, and textural properties. Compared to the control samples, extrudates supplemented with mushroom powder showed a reduced product expansion, decreased water absorption index, increased water solubility index and altered microstructure characteristics. Differences in starch gelatinisation and starch hydrolysis resulted in a reduced predictive glycaemic response value for mushroom supplemented extrudates. Inclusion of mushroom material resulted in higher levels of phenolic compounds and antioxidants. Highlights: Incorporation of mushroom altered the physical and textural properties of hot extruded products. Incorporation of mushroom increased the insoluble and total dietary fibre, but reduced starch content of final products. Addition of mushroom limited the starch gelatinisation and digestibility of hot extruded products. Addition of mushroom enhanced the antioxidant abilities of hot extruded snacks.